Analysis of dengue virus vector control causing dengue hemorrhagic fever (DHF) in high and low case - Oktafiani, Devi; Intania Riska Putrie; Fakhriah M. Samiun (Sean Institute, 2024)
Dengue Hemorrhagic Fever is still a global public health problem, especially in tropical and subtropical regions, including Indonesia as one of the dengue-endemic countries. Central Sulawesi is one of the endemic areas of dengue fever in Indonesia. DHF cases in Central Sulawesi Province are recorded to fluctuate every year and the morbidity rate tends to increase. In the Palu city area, Birobuli Selatan Village is the area with the highest cases, while in the Nunu Village, no dengue cases were detected. This research method is to use a questionnaire to look at the habits of people in areas with low cases and high cases in controlling disease vectors. Data analysis used the chi-square test. The research results showed that in the group of areas with high cases, there were differences in 3M habits (p=0.021), use of mosquito nets (p=0.000), plants around the house (p=0.000), and residential density (p<0.05). Meanwhile, there is no difference in the use of mosquito repellent and abate in the two regions. This research concludes that there are differences in people's habits regarding activities or activities in controlling mosquito vectors that cause dengue fever in areas with high cases and low cases